Large-Scale Transformation of Socio-Economic Institutions - Comparative Case Studies on CEECs. Background Paper 1: Comparative Country Study - Slovakia - Ivana Sikulová; Karol Frank (WWWforEurope, 2013)
The general idea is to follow the Varieties-of-Capitalism literature on generating indicators on the economic systems actually implemented. However, this literature mostly concentrates on the enterprise (or micro) level in traditional OECD countries, categorizing countries between the extremes: liberal market economies and controlled market economies. It largely neglects the role of the government spending, the transition of former socialist countries and developing countries, and the political process behind the choice of an economic system. We broaden the perspective by combining the Varieties-of-Capitalism with the Worlds-of-Welfare-States literature in order to provide a comprehensive view on government activities in transition. With the perspective of our contribution to WWWforEurope, we concentrate especially on social welfare, innovation systems, macro stability, and, of course, how these aspects work together (or not) and are explained by the political background. We will a cluster analysis for OECD and European transition countries and comparative country studies on Slovakia and Hungary. These countries are of special relevance because they represent extreme cases (Slovakia: significant switch in transition path towards star performer, Hungary: muddling towards problem case). One part of the comparative work concentrates on the comparison of Slovakia with other new EU members that also face to challenge of state building after dissolution of one or the other sort (Czech Rep. and the Baltics). The other part of the comparative work concentrates on Hungary in comparison with the other EU-CEECs. A broad based comparison will most likely be possible on available data only. The possibility for deeper qualitative comparisons will have to be determined during the project. The comparative components will focus on the macroeconomic background (Slovakia) and the welfare state (Hungary) respectively. Cluster analysis (initially forseen for MS25) and comparative country studies allows us to draw conclusions for the EU by providing a first comparison of the position of CEECs with respect to the “old” EU members, most interestingly the southern crisis countries that are often categorized into a form called mixed market economies with sometimes contradicting institutional set ups. Do CEECs converge towards prototype models or do they (still) constitute own models?
Keywords: P10; P51; 330; EU integration; innovation; innovation policy; institutional reforms; macroeconomic disequilibria; market economy with adjectives; social development; welfare reform; welfare state